IMPLEMENTASI METODE BRAINSTORMING DALAM MENINGKATKAN KREATIFITAS BERPIKIR DAN KEMAMPUAN KOLABORATIF SISWA MTs AL-ISHLAH PANAMBANGAN - Moh Noerfiadi; Septi Gumiandari (JIP: Jurnal Ilmu Pendidikan, 2024)
The objective of this study is to determine the effect of the brainstorming method on enhancing creative thinking and collaborative skills of students at MTs Al-Ishlah Panambangan. The method used in this research is quantitative with a quasi-experimental approach. The type of data used is quantitative data, and the source of data is primary data. The data analysis technique employed is the independent sample t-test. The results of the study indicate that brainstorming has an effect on the creativity and collaborative abilities of students at MTs Al-Ishlah Panambangan.